SOCIAL STIGMA AND IMPRESSION MANAGEMENT: A PHENOMENOLOGICAL STUDY OF THE WIVES OF FORMER GEMBLAK IN JAVANESE CULTURE - Cycy Annisa; Rizal Mummaziq Jiyonis; Zulaihin Frendi Nuraini; Andhita Risko Faristiana; Sri Sukamto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study discusses the experiences of former gemblak wives in interpreting their husbands' past, as well as the forms of social stigma and impression management strategies they employ in their daily lives. The tradition of gemblakan, which was once accepted as part of the culture and spirituality of warok, has undergone a change in meaning with the development of religious values, modernity, and shifts in the representation of Reyog Ponorogo art. Using Alfred Schutz's phenomenological approach, this study explores how the meaning of experience is formed through intersubjectivity and the Javanese cultural lifeworld, which emphasizes an attitude of acceptance. Meanwhile, Erving Goffman's theory of stigma and impression management is used to analyze how former gemblaks and their families deal with negative labeling from society. The results of the study show that the wives of former gemblak are able to negotiate their husbands' past through cultural acceptance, social adaptation, and family image management strategies in order to maintain harmony and acceptance within their social environment. These findings confirm that cultural dynamics, modern values, and subjective experiences play an important role in shaping the family's response to social stigma.